Detection of early cardiac disease manifestation in propionic acidemia - results of a monocentric cross-sectional study - Kovacevic, Alexander; Garbade, Sven; Hörster, Friederike; Hoffmann, Georg F.; Gorenflo, Matthias; Mereles, Derliz; Kölker, Stefan; Staufner, Christian (Molecular genetics and metabolism, 2022)
Background - In propionic acidemia (PA) myocardial involvement is common and includes development of cardiomyopathy, life-threatening acute heart failure, and acquired long-QT syndrome. We sought to investigate which echocardiographic parameters of left ventricular systolic and diastolic function indicate early cardiac disease manifestation in PA. - Methods - This is a prospective observational study (cross-sectional design) in a Tertiary Medical Care Center. Individuals with confirmed PA were enrolled and the following cardiac investigations were performed in all study individuals: echocardiographic measurements of systolic and diastolic left ventricular (LV) function (LV fractional shortening (LV-FS), LV ejection fraction by biplane modified Simpson's (LV-EF), mitral annular plane systolic excursion (MAPSE), LV global longitudinal strain (LV-GLS) by speckle tracking echocardiography (STE), pulsed Doppler analyses of mitral valve (MV) inflow velocities (MV E/A) and MV deceleration time (DT-E), tissue doppler imaging (TDI) of the mitral annulus (MV E/e'), and LV myocardial performance index (LV-MPI)). LV and left atrial (LA) diameters were assessed. 12‑lead electrocardiograms (ECG) were recorded and corrected QT intervals (QTc) calculated. Clinical phenotype and laboratory parameters at the time of cardiac investigation were assessed. Besides descriptive analyses we analyzed frequency, onset, and combinations of echocardiographic and ECG data as well as their correlations with clinical and biochemical findings. The effects of ‘age at visit’ and LV functional parameters on QTc were analyzed with multiple regression. - Results - A total of 18 patients with confirmed PA were enrolled. Median age at PA onset was 6 days (range 1-357 days). Median age at visit for cardiac evaluation was 13.1 years (range 0.6-28.1 years). LV-GLS was abnormal in 72.2%, LV-EF in 61.1%, MAPSE in 50%, MV E/e' in 44.4%, LV-MPI in 33.3%, LV-FS in 33.3%, and MV E/A in 27.8%. In cases with normal or near normal LV-FS, LV-GLS was pathological in 5/10, LV-EF in 4/10, and MAPSE in 3/10. The probability of developing LV dysfunction - systolic and diastolic - increases with age. LV-MPI is a reliable parameter to indicate systolic LV-dysfunction in combination with a dilated LV, i. e. dilated cardiomyopathy (DCM) in PA. Multiple regression reveals a significant positive association between LV diameters and QTc. Abnormal LV-GLS significantly correlates with reduced muscle strength, muscle tone and/or abnormal gross motor function. - Conclusions - Our data suggests a high prevalence of cardiac disease manifestation in PA, considerably higher than in previous studies, where only LV-FS was used to assess LV function. Usage of advanced echocardiographic techniques, such as LV-GLS assessment, may allow for early detection of subtle LV dysfunction in PA, and may lead to timely cardiac treatment but also consideration of liver transplantation to prevent development of manifest cardiac complications.